Estimation of the efficiency of the herbicide ‘Axial Cross’ for grain crops - A. S. Golubev (Зерновое хозяйство России)
The current paper has presented the results of a two-year study (2018–2019), the purpose of which was to study the efficiency of the herbicide ‘Axial Cross, EC’ (45 g/l of pinoxaden + 5 g/l of florasulam + 11.25 g/l of antidote cloquintoset-mexil) in 6 regions of the Russian Federation, namely on the crops of winter wheat variety ‘Ershovskaya’ in the Volgograd region, on the crops of winter wheat varieties ‘Skipetr’ (2018) and ‘Snigurka’ (2019) in the Voronezh region, on the crops of spring wheat variety ‘Altaiskaya Zhnitsa’ in the Altai Territory, on the crops of spring wheat variety ‘Uralosibirskaya’ in the Omsk Region, on the crops of spring barley variety ‘Acha’ in the Sverdlovsk Region, on the crops of winter barley variety ‘Rubezh’ in the Krasnodar Territory. The trials were laid on plots of 25 m2 in four sequences. The weed infestation of crops was estimated by a quantitative method before the treatment, in 30 and 5 days after it and before harvesting. The efficiency of the herbicide was calculated in relation to the untreated control. There has been established that the use of ‘Axial Cross, EC’ at application rates of 0.7–0.9–1.1 l/ha has provided a high degree of suppression of both cereals and dicotyledonous weeds. At the maximum rate of application, there was a 100 % efficiency of the herbicide against yellow-foxtail grass, wild oats, green-foxtail grass, blind weed, canker rose and black bindweed, 97.4 % against loose silky bent, 95.6 % against airif (catchweed). There was up to 68.1–77.7 % efficiency against Canadian thistle, corn sow thistle and field bindweed. The greatest yield increase after the use of the herbicide ‘Axial Cross, EC’ was obtained from the winter wheat varieties ‘Skipetr’ (0.88 t/ha) and ‘Snigurka’ (1.65 t/ha) in the Voronezh region.